Artificial intelligence and public sector human resource management in South Africa: Opportunities, challenges and prospects - Alouis Chilunjika; Kudakwashe Intauno; Sharon R. Chilunjika (AOSIS, 2023)
Orientation: The Fourth Industrial Revolution has transformed modern society by ushering in the fusion of advances in robotics, the Internet of Things (IoT), genetic engineering, quantum computing, and artificial intelligence (AI) among others. AI brings a range of different technologies and applications to interact with environments that comprise both the relevant objects and the interaction rules and have the capacity to process information in a way that resembles intelligent behaviour. Similarly, artificial intelligence is also being used in the human resources management (HRM) processes and functions in the public sector to map sequences to actions.